The Accessibility Analysis for The Special Needs Students in Lambung Mangkurat - Utomo, Utomo; Suratno, Suratno (Journal of ICSAR, 2019)
The accessibility of building and environment is a part of the effort to fulfill the rights for disabilities. The people with disabilities is that every person who have the physical impirment, intelectual, mental, and also the sensoric for a long time which obstacle their interaction with the environment to fully participate. This research conducted to identify the condition and the availability of the building and environment in Lambung Mangkurat University. This research are conducted in 24 point of location which spread on 11 faculties in Banjarbaru and Banjarmasin regio and using the qualitative method and descriptive-analitic approach.The data collection technique in this research is that observation, measurement, and direct interview to the subject of the research. The result of this research will be a  recommendation that can be a consideration to the stake holder to fulfilling the right of disabilities regarding the building and environment ini Lambung Mangkurat University.